Legal Protection For Honorer Employment Due To Dissolution Of Nonsstructural Institutions - Handoko, Panggung (International Journal of Educational Research & Social Sciences, 2023)
Honorary workers are one of the problems in the staffing aspect in Indonesia. The issuance of Law Number 5 of 2014 concerning State Civil Apparatus (UU ASN) has greatly affected the status and legal protection of honorary workers. This research examines the legal vacuum and legal protection for temporary workers due to the dissolution of the Nonstructural Institution (LNS). The policy of dissolving the LNS resulted in a legal vacuum and required legal protection for temporary workers working at the LNS. The research method used in this research is normative juridical. This research uses the Legislative Regulation approach(Statue Approach) and Conceptual Approach(Conceptual Approach). The legal material used in this study comes from primary, secondary and tertiary sources. Thus the ASN Law and its implementing regulations should be able to provide protection for honorary workers due to the impact of the dissolution of the LNS. The results of this study indicate that temporary workers experience a legal vacuum and need legal protection. Based on these results, honorary workers need regulations that specifically regulate honorary workers affected by the dissolution of the LNS and honorary workers are entitled to legal protection.preventivenamely preventing termination of employment and legal protectionrepressive, namely resolving disputes where there is no common ground between the parties carried out through the courts.